The Effect Of Different Solvent Extraction On Chemical Content And Quercetin Levels Of Ketapang (Terminalia cattapa L.) - Erma Yunita; Erlinda Mula Destasary; Fa’iz Helmi Wicaksana (Jurnal Farmasi (Journal of Pharmacy), 2021)
Ketapang has flavonoid content that is quercetin. The appropriate solvent can attract the active compound of quercetin on ketapang. The selection of solvents adjusts different levels of polarity with the aim of obtaining the best solvent. This study aims to determine the difference between extraction solvents to the quercetin levels of ketapang leaves.Simplisia leaves of ketapang made by winding. Maceration is carried out on ketapang leaves using 3 different solvents namely n-hexane, ethyl acetate, and ethanol 90%. The viscous extract obtained was analyzed for yield value and the phytochemical screening test was do qualitatively. Quercetin level measured by UV-Vis Spectrophotometry at a maximum wavelength of 375.6 nm. The absorbance value obtained is entered into the standard quercetin curve equation with the equation y=0.0885x+0.0037.The results of the yield value of ketapang leaf extracts with each different type of solvent resulted in different yield values, as well as the results of phytochemical screening and percent quenching levels obtained.Keywords: Terminalia cattapa L., Yield Extract, Phytochemical, Quercetin